Post-COVID Reflections and Practice from the Oral Surgeon's Perspective - Babatunde Bamgbose; A Yahaya (Nigerian Dental Association, 2023)
Introduction Globally, the post-COVID era has afforded practitioners the opportunity to evaluate the quality assurance measures for continued safe service delivery. The preventive measures against COVID-19 have been relaxed and most intense care units and hospital bed spaces dedicated to the management of COVID-19 cases have been relaxed or, in some places, closed. Methods The study was conceptualized as a narrative review of focal literature that focused on the COVID-19 and its impact on the practice of oral and maxillofacial surgery and dentistry. The study built a synthesis to describe the post-COVID era and the reflections on dental practice and oral and maxillofacial surgery. Literature searches were carried out using PubMed and Google Scholar with no search filters, using Boolean Logic ''AND'' and ''OR.'' Searches of the literature cited by eligible studies were also performed. Expert opinion There is the assumption that all trainers and trainees have been vaccinated and less at risk of contracting COVID-19 and Oral and Maxillofacial Surgical training has returned to the pre-COVID approach where physical contact and bedside teachings are no longer restricted. All specialties of dentistry conduct training programs with minimal restrictions on physical contact and one-one interactions between trainers and trainees.  Keywords: Coronavirus, WHO, Aerosols, Patient services, Training, Post-COVID